Behavior Control Reflected In Okky Madasari's The YearsOf The Voiceless Novel (2013): An Individual Psychological Approach - Mujtahid, Nito Majid, Dr. Phil. Dewi Candraningrum, M.Ed (2017)
The study is human behavior control reflected in Okky Madasari's The Years of the Voiceless (2013). The research is proposed to analyze behavior control of Sumarni's character in The Years of The Voiceless Novel using Individual Psychological Approach. The writer use descriptive qualitative study that has two types of data which needed to conduct the research. The first is primary data of The Years of The Voiceless Novel (2013) by Okky Madasari. The secondary object is any references from books, journals and articles that related to the study. The technique of collecting data is using Library Research and Note-taking method. In order to analyze The Years of The Voiceless novel, the researcher used Individual Psychological Approach by Alfred Adler because it is relevant to the problem that the researcher want to analyze Sumarni as the main character using six points i.e. fictional finalism, inferiority feeling, striving for superiority, social interest, style of life and creative power or self. Based on the analysis, the researcher took a conclusion. Sumarni behavior control arise when her desire arise but she cannot afford it because her lack of power. The most human behavior control related in the human life as the conclusion of Individual Psychological Approach about human beings.